Behavioral and psychosocial interventions for HIV prevention in floating populations in China over the past decade: a systematic literature review and meta-analysis. - Xiaona Liu; Vicki Erasmus; Qing Wu; Jan Hendrik Richardus (PLoS ONE)
Background Floating populations have been repeatedly characterized as "the tipping point" for the HIV epidemic in China. This study aims to systematically summarize and assess the effectiveness of HIV prevention interventions in floating populations in China over the past decade. Methods We conducted a systematic search in three international databases for literature published between 2005 and 2012 with condom use as the primary outcome, and knowledge about HIV transmission and prevention and stigma towards HIV-infected individuals as secondary outcomes. The impact of interventions on changing the primary and secondary outcomes was calculated by risk difference (RD). We also performed subgroup analyses and meta-regression based on different study characteristics, using Stata 12.0, for the primary outcome. Results Sixteen studies (out of 149) involved 19 different programs and a total of 10,864 participants at entry from 11 provinces in China. The pooled effect estimate of all studies indicated that people participating in HIV-related interventions were 13% more likely to use condoms (95%CI: 0.07, 0.18), however, the effects on increasing condom use exhibited significant heterogeneity across programs (P<0.01, I2 = 0.93). The meta-regression results suggest that interventions have been significantly less successful in changing condom use in more recent studies (β, 0.14; 95%CI: 0.01, 0.27), adjusted for sexual relationship, study design and follow-up period. Regarding the secondary outcomes, HIV-related interventions were successful at improving knowledge about HIV transmission and prevention (RD, -0.26; 95%CI: -0.36, -0.16 and RD, -0.25; 95%CI: -0.33, -0.16, respectively), and decreasing stigma (RD, 0.18; 95%CI: 0.09, 0.27). Conclusions The included studies between 2005 and 2012 indicate that HIV prevention interventions among Chinese floating populations in the past decade were only marginally effective at increasing condom use, but relatively successful at increasing HIV knowledge and decreasing stigma. To avert new infections, novel sexual risk-reduction interventions taking into account the changing socio-economic and cultural situation of Chinese floating populations are urgently needed.